L‐Methionine anti‐biofilm activity against Pseudomonas aeruginosa is enhanced by the cystic fibrosis transmembrane conductance regulator potentiator, ivacaftor. Issue 5 (7th February 2018) - Cho, Do‐Yeon; Lim, Dong‐Jin; Mackey, Calvin; Weeks, Christopher G.; Peña Garcia, Jaime A.; Skinner, Daniel; Grayson, Jessica W.; Hill, Harrison S.; Alexander, David K.; Zhang, Shaoyan; Woodworth, Bradford A.
Abstract : Background: Biofilms may contribute to refractory chronic rhinosinusitis (CRS), as they lead to antibiotic resistance and failure of effective clinical treatment.l ‐Methionine is an amino acid with reported biofilm‐inhibiting properties. Ivacaftor is a cystic fibrosis transmembrane conductance regulator (CFTR) potentiator with mild antimicrobial activity via inhibition of bacterial DNA gyrase and topoisomerase IV. The objective of this study was to evaluate whether co‐treatment with ivacaftor andl ‐methionine can reduce the formation of Pseudomonas aeruginosa biofilms. Methods: P aeruginosa (PAO‐1 strain) biofilms were studied in the presence ofl ‐methionine and/or ivacaftor. For static biofilm assays, PAO‐1 was cultured in a 48‐well plate for 72 hours with stepwise combinations of these agents. Relative biofilm inhibitions were measured according to optical density of crystal violet stain at 590 nm. Live/dead assays (BacTiter‐Glo™ assay, Promega) were imaged with laser scanning confocal microscopy. An agar diffusion test was used to confirm antibacterial effects of the drugs. Results: l ‐Methionine (0.5 μM) significantly reduced PAO‐1 biofilm mass (32.4 ± 18.0%; n = 4; p < 0.001) compared with controls. Low doses of ivacaftor alone (4, 8, and 12 μg/mL) had no effect on biofilm formation. When combined with ivacaftor (4 μg/mL), a synergistic anti‐biofilm effect was noted at 0.05 μM and 0.5 μM ofl ‐methionine (two‐way analysis of variane, p = 0.0415) compared with corresponding concentrations ofl ‐methionine alone. Conclusion: Ivacaftor enhanced the anti‐biofilm activity ofl ‐methionine against the PAO‐1 strain of P aeruginosa . Further studies evaluating the efficacy of ivacaftor/l ‐methionine combinations for P aeruginosa sinusitis are planned.